Uwagi na temat uwarunkowań polityki karnej realizowanej przez sądy na przykładzie stosowania art. 178a § 2 k.k. i art. 62–62a ustawy z 2005 roku o przeciwdziałaniu narkomanii - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The author of the study joins the discussion on the factors shaping the criminal policy characteristic for the period of validity of the Penal Code of 1997. She does so based on a selected fragment of the legal reality, outlining the impact of the criminal legislation on the criminal policy in terms of implementation of the latter by the courts. The author uses the example of the regulations of Article 178a § 2 of the Criminal Code and Articles 62–62a of the 2005 law on Counteracting Drug Addiction concerning their normative and practical terms. Analysing the crimes indicated, which belong to common behaviours, She reﬂects on the complexity of relations between the written law and the law in action. In conclusion, the author emphasises that it is the law in action and the examination of its results that reﬂ ects factors that have speciﬁc signiﬁcance for the shaping of penal policy.
Keywords: przestępczość; kara; polityka karna; przeciwdziałanie narkomanii; zatrucie; prowadzenie pojazdu mechanicznego